Drosha-independent miR-6778–5p strengthens gastric cancer stem cell stemness via regulation of cytosolic one-carbon folate metabolism. (28th May 2020) - Zhao, Maojia; Hou, Yixuan; Du, Yan-e; Yang, Liping; Qin, Yilu; Peng, Meixi; Liu, Shuiqing; Wan, Xueying; Qiao, Yina; Zeng, Huan; Cui, Xiaojiang; Teng, Yong; et al.
Abstract: Drosha-dependent canonical microRNAs (miRNAs) play a crucial role in the biological functions and development of cancer. However, the effects of Drosha-independent non-canonical miRNAs remain poorly understood. In our previous work, we found a set of aberrant miRNAs, including some upregulated miRNAs, called Drosha-independent noncanonical miRNAs, in Drosha-knockdown gastric cancer (GC) cells. Surprisingly, Drosha-silenced GC cells still retained strong malignant properties (e.g., proliferation ability and cancer stem cell (CSC) characteristics), indicating that aberrantly upregulated non-canonical miRNAs may play an important role in the maintenance of the malignant properties in GC cells that express low Drosha levels. Here, we report that miR-6778–5p, a noncanonical miRNA, acts as a crucial regulator for maintenance of CSC stemness in Drosha-silenced GC cells. MiR-6778–5p belongs to the 5′-tail mirtron type of non-canonical miRNAs and is transcript splice-derived from intron 5 of SHMT1 (coding cytoplasmic serine hydroxymethyltransferase). It positively regulates expression of its host gene, SHMT1, via targeting YWHAE in Drosha-knockdown GC cells. Similar to its family member SHMT2, SHMT1 plays a crucial role in folate-dependent serine/glycine inter-conversion in one-carbon metabolism. In Drosha wild type GC cells, SHMT2 mediates a mitochondrial-carbon metabolic pathway, which is a major pathway of one-carbon metabolism in normal cells and most cancer cells. However, in Drosha-silenced or Drosha low-expressing GC cells, miR-6778–5p positively regulates SHMT1, instead of SHMT2, thus mediating a compensatory activation of cytoplasmic carbon metabolism that plays an essential role in the maintenance of CSCs in gastric cancer (GCSCs). Drosha wild type GCSCs with SHMT2 are sensitive to 5-fluorouracil; however, Drosha low-expressing GCSCs with SHMT1 are 5-FU-resistant. The loss of miR-6778–5p or SHMT1 notably mitigates GCSC sphere formation and increases sensitivity to 5-fluorouracil in Drosha-knockdown gastric cancer cells. Thus, our study reveals a novel function of Drosha-independent noncanonical miRNAs in maintaining the stemness of GCSCs. Highlights: Enhanced noncanonical miRNA6778-5p plays a pivotal role in the malignant properties of Drosha-low expressed gastric cancer (GC). The 5'-tail mirtron miR-6778-5p can feedback regulate host gene SHMT1 expression via targeting YWHAE to relieve its inhibitory effect on c-MYC. SHMT1-mediated cytoplasmic one-carbon metabolism plays an essential role in maintenance of gastric cancer stem cell (GCSC). Drosha wild type GCSC with SHMT2 is sensitivity to 5-fluorouracil, and Drosha low expressed GCSC with SHMT1 endows the GCSC with 5-FU-resistance. Impeding miRNA6778-5p/YWHAE/SHMT1 signaling axis can enhance sensitivity of gastric cancer to 5-FU chemotherapy.